Implementing cultural policies in universities of medical sciences: a model with mediating role of spirituality - Amirmohammadi , Eraj; Manzari Tavakoli, Alireza; Salajegheh , Sanjar; Mehdizadeh, Samaneh (Social Determinants of Health, 2021)
Introduction: The aim of this study was to present a model for the implementation of cultural policies in relation to organizational culture with an emphasis on the mediating role of spirituality and mental health in universities of medical sciences. Methods: The present study was descriptive-correlational research. The data collection method was a combination of library and field studies and the data collection instruments included a review of documents, interviews and a researcher-made Cultural Policy Questionnaire, Workplace Spirituality Questionnaire, and Organizational Culture Questionnaire. The statistical population included 21496 hospital staffs and managers of medical sciences hospitals. Since structural equation modeling approach was used in this study, finally 472 people were statistically analyzed. The samples were determined using a stratified sampling method. In the present study, SPSS-23 and AMOS-24 software was used to analyze the data. Results: The research results confirmed the proposed research model and indicated a significant relationship between cultural policies and spirituality in university hospitals. Given the positive path coefficient, this relationship is direct. Based on the coefficient of determination (R2), 44% of spirituality changes in the hospital are explained by cultural policies. In addition to having a direct effect, cultural policies indirectly affect organizational culture through workplace spirituality. The level of direct impact was equal to 0.129 and the level of indirect impact through workplace spirituality was equal to 0.204. Conclusion: A direct relationship was between cultural policies and organizational culture and an indirect relationship between spirituality in university hospitals and organizational culture.